Links between metamorphosis and symbiosis in holometabolous insects. (26th August 2019) - Hammer, Tobin J.; Moran, Nancy A.
Abstract : Many animals depend on microbial symbionts to provide nutrition, defence or other services. Holometabolous insects, as well as other animals that undergo metamorphosis, face unique constraints on symbiont maintenance. Microbes present in larvae encounter a radical transformation of their habitat and may also need to withstand chemical and immunological challenges. Metamorphosis also provides an opportunity, in that symbiotic associations can be decoupled over development. For example, some holometabolous insects maintain the same symbiont as larvae and adults, but house it in different tissues; in other species, larvae and adults may harbour entirely different types or numbers of microbes, in accordance with shifts in host diet or habitat. Such flexibility may provide an advantage over hemimetabolous insects, in which selection on adult-stage microbial associations may be constrained by its negative effects on immature stages, and vice versa. Additionally, metamorphosis itself can be directly influenced by symbionts. Across disparate insect taxa, microbes protect hosts from pathogen infection, supply nutrients essential for rebuilding the adult body and provide cues regulating pupation. However, microbial associations remain completely unstudied for many families and even orders of Holometabola, and future research will undoubtedly reveal more links between metamorphosis and microbiota, two widespread features of animal life. This article is part of the theme issue 'The evolution of complete metamorphosis'.